(untitled) (World Bulletin of Public Health, 2021)
Cardiovascular disease (CVD) is one of the leading causes of death and disability worldwide. Rheumatoid arthritis is a common chronic connective tissue disease in adults and children, which leads to destruction of symmetrical joints. According to the European Society of Cardiology, "...over 4 million people die each year from CVDs, of which 1.4 million under 75 years old, accounting for 45% of all deaths...". According to major research centres, cardiovascular mortality (CVD) is more common in patients with rheumatoid arthritis (RA) than in the general population